Efeito da aplicação prolongada do sistema adesivo convencional de dois passos na qualidade de restaurações de resina composta em lesões cervicais não cariosas: Ensaio clínico controlado, randomizado, duplo cego - Camargo, Márcio Neves (2018)
This double-blind randomized clinical trial evaluates the influence of increased application time in two adhesive system two-step etch-and-rinse (Peak® Universal Bond (P); Ultradent Products Ind and Single Link (SL); Angelus Dental Products Industry) applied in non-carious cervical lesions (NCCLs). Methods: A total of 219 restorations were randomly placed in 35 patients according to the following groups: P1 - applied according to the manufacturer’s; P2X – applied for the double time; SL1 and SL2X (the same application mode). The resin composite Amelogen (Ultradent) was placed incrementally. The restorations were evaluated immediately (baseline) and 6 months, using the FDI and USPHS criteria. Statistical analyses were performed using appropriate tests (=0.05). Results: Twenty-four restorations were lost at 6 months (4 for P1, 2 for P2X, 9 for SL1 and 9 for SL2X) (p < 0.05 between groups). Post-operative sensitivity wasn’t observed in any of the recall periods. Thrity-five restorations were considered to have minor discrepancies in marginal adaptation at the 6-month recall using the FDI criteria (8 for P1, 7 for P2X, 12 for SL1 and 8 for SL2X; p > 0.05 between groups). Ten restorations were considered to have minor discrepancies in marginal discoloration at the 6-month recall (2 for P1, 1 for P2X, 3 for SL1 and 2 for SL2X; p > 0.05 between groups). Conclusion: The increased application time of adhesive system two-step etch-and-rinse didn’t improve the clinical behavior of composite restorations placed in NCCLs. In the meantime, clinical behavior may be influenced by the composition of adhesive systems.